2022
DOI: 10.1002/pd.6159
|View full text |Cite
|
Sign up to set email alerts
|

Factors that impact on women's decision‐making around prenatal genomic tests: An international discrete choice survey

Abstract: Objective: We conducted a survey-based discrete-choice experiment (DCE) to understand the test features that drive women's preferences for prenatal genomic testing, and explore variation across countries.Methods: Five test attributes were identified as being important for decisionmaking through a literature review, qualitative interviews and quantitative scoring exercise. Twelve scenarios were constructed in which respondents choose between two invasive tests or no test. Women from eight countries who delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 63 publications
1
27
1
Order By: Relevance
“…Previous studies, including our own, show that pregnant women who undergo prenatal diagnosis for a range of indications largely support the disclosure of all types of CMA findings, including VUS and SL 9,11–13 . However, studies exploring parents' experience with receiving uncertain CMA results showed that parents can experience shock, anxiety, and a need for support 14–19 …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies, including our own, show that pregnant women who undergo prenatal diagnosis for a range of indications largely support the disclosure of all types of CMA findings, including VUS and SL 9,11–13 . However, studies exploring parents' experience with receiving uncertain CMA results showed that parents can experience shock, anxiety, and a need for support 14–19 …”
Section: Introductionmentioning
confidence: 78%
“…Previous studies, including our own, show that pregnant women who undergo prenatal diagnosis for a range of indications largely support the disclosure of all types of CMA findings, including VUS and SL. 9,[11][12][13] However, studies exploring parents' experience with receiving uncertain CMA results showed that parents can experience shock, anxiety, and a need for support. [14][15][16][17][18][19] Limited data are available on the effect of uncertain findings (VUS and SL) on decisions concerning the continuation of pregnancies and factors affecting these decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our and others' previous works, 7,27,31,36 when women are given a choice regarding CMA findings, they are more likely to request all types of results, including uncertain information, rather than avoid such results. It could therefore be assumed that stratified choice would seem unnecessary for some women/couples.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of evidence about how women want to receive information about NIPT and few studies have been conducted in Sweden. An international DCE study quantified preferences of a sample of women from different countries (including Sweden) for factors that affect their decision‐making around prenatal genomic tests 16 . However, this study assessed preferences for testing, not information provision.…”
Section: Introductionmentioning
confidence: 99%
“…An international DCE study quantified preferences of a sample of women from different countries (including Sweden) for factors that affect their decision‐making around prenatal genomic tests. 16 However, this study assessed preferences for testing, not information provision. Understanding how to effectively communicate the information to expectant mothers may mean policy makers can provide details in a way that maximises benefit to the mother and baby alike.…”
Section: Introductionmentioning
confidence: 99%